Financial Resources and Firm Performance - Sari, Tyasha Ayu Melynda; Ainun, Moh. Baqir (Politeknik Ganesha Medan, 2024)
This research aims to determine the effect of financial resources on company performance. This research uses a sample of manufacturing companies listed on the Indonesia Stock Exchange 2016-2022. Company resources become an important part of the development the company, especially financial resources which are the main factor in carrying out the company's operational activities. The company's performance becomes benchmark for investors and creditors to assess the company's condition. The company's financial resources in this research come from cash flow, liquidity, and leverage. Cash flow used financial analysis to determine the income and expenses made by the company. Liquidity used to assess the company's ability to meet its obligations. Leverage as company debt used to finance and purchase company assets. The results showed that only free cash flow had significant effect on company performance. This happens because the company's performance is reflected in the higher will increase the amount of profit earned by investors. This shows that the company utilizes ability of the company's internal resources to utilize financial resources to create competitive advantage so that the company's performance can manage its cash flow to finance assets owned by the company. The results of this research support the resource-based theory-based view.